Variability in changes of acrylamide precursors during nixtamalization for masa production. (1st May 2022) - Renk, Jonathan S.; Burns, Michael J.; Gilbert, Amanda M.; Anderson, Nickolas; Waters, Amanda J.; Eickholt, David P.; Kalambur, Sathya; Annor, George A.; Hirsch, Candice N.
Abstract: Consumption of corn-based foods is increasing in the United States and globally. Little is known about changes in kernel compositional profiles, including levels of acrylamide precursors (e.g. asparagine and reducing sugars), when corn kernels are cooked in a process called nixtamalization. The objectives of this study were to investigate the compositional variation of raw starting materials, general compositional changes during nixtamalization, and genotype specific patterns of change for acrylamide precursors during this process. A panel of 120 genotypes were subject to a small-scale bench top cooking protocol to investigate compositional changes that occur during cooking and steeping. Substantial variation was observed in the raw starting material for all compositional traits that were measured including asparagine, fructose, glucose, crude protein, and starch. During nixtamalization a decrease in asparagine, glucose, and fructose mean and variation was observed, while crude protein and starch remained relatively stable. Analysis of the genotype-by-subsample interactions (after cooking and after steeping) revealed variation in compositional changes in response to cooking among the genotypes. These findings reveal the dynamics of compositional traits during nixtamalization of corn kernels. This information can be used by plant breeders and food processors to more effectively make acrylamide mitigation strategies. Highlights: There was significant variation in the raw material for acrylamide precursors. There was variability in chemical changes in response to the cooking process. Nixtamalization decreased overall mean and variance for acrylamide precursors.